The α(2)δ-1 subunit remodels Ca(V)1.2 voltage sensors and allows Ca(2+) influx at physiological membrane potentials - Savalli, Nicoletta (J Gen Physiol, 2016)
Excitation-evoked calcium influx across cellular membranes is strictly controlled by voltage-gated calcium channels (Ca(V)), which possess four distinct voltage-sensing domains (VSDs) that direct the opening of a central pore. The energetic interactions between the VSDs and the pore are critical for tuning the channel’s voltage dependence. The accessory α(2)δ-1 subunit is known to facilitate Ca(V)1.2 voltage-dependent activation, but the underlying mechanism is unknown. In this study, using voltage clamp fluorometry, we track the activation of the four individual VSDs in a human L-type Ca(V)1.2 channel consisting of α(1C) and β(3) subunits. We find that, without α(2)δ-1, the channel complex displays a right-shifted voltage dependence such that currents mainly develop at nonphysiological membrane potentials because of very weak VSD–pore interactions. The presence of α(2)δ-1 facilitates channel activation by increasing the voltage sensitivity (i.e., the effective charge) of VSDs I–III. Moreover, the α(2)δ-1 subunit also makes VSDs I–III more efficient at opening the channel by increasing the coupling energy between VSDs II and III and the pore, thus allowing Ca influx within the range of physiological membrane potentials.